A method for the continuous monitoring of reactivity in subcritical source-driven systems. (January 2016) - Dulla, S.; Nervo, M.; Ravetto, P.
Highlights: The problem of the reactivity monitoring in subcritical accelerator-driven systems is studied. An inverse method, based on point kinetics, for the determination of the reactivity is applied to source-driven systems. The technique is applied to different transient situations, proving its accuracy in the presence of localized spatial and spectral phenomena. Different approaches for the reduction of the experimental noise are proposed. Abstract: The reactivity monitoring in subcritical accelerator-driven systems is a key aspect for the development of this technology. In this work, an inverse method for the determination of the system reactivity from the analysis of flux and power signals, based on the point kinetic approach, is applied to source-driven systems. The features of the algorithm specific to the application to subcritical assemblies are identified, and the sensitivity to the integral parameters characterizing the system is discussed. The technique is applied to different transient situations, simulated by neutronic codes adopting point kinetics and multigroup diffusion, and its accuracy in the presence of localized spatial and spectral phenomena is assessed. Different approaches for the reduction of the uncertainties introduced by the experimental noise are proposed and compared.